Analisis Laporan Keuangan dalam Menilai Kinerja Keuangan Industri Rokok yang Terdaftar di BEI (Studi Kasus PT Gudang Garam Tbk pada Periode 2019-2023) - Rizki Setia Rini; Saras Supeno; Vela Hani Choerunnisa; Sania Ferika (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research is motivated by the revenue of PT Gudang Garam Tbk, which experienced an increase from 2019 to 2022 but declined in 2023, accompanied by fluctuating operating expenses that tend to decrease. However, when examining net income before tax and net income after tax, there has been a decline for four consecutive years, followed by an increase in 2023. The purpose of this study is to analyze the financial performance of PT Gudang Garam Tbk for the period 2019-2023 based on the Current Ratio, Quick Ratio, Cash Ratio, Return on Assets, and Return on Equity. The results of the study indicate that the current ratio of the company’s financial ratios is unstable. The quick ratio shows that the company’s condition is not good, as it still struggles to meet its short-term obligations quickly. The cash ratio indicates that the company’s cash ratio is below the industry standard. Return on assets shows that financial performance has declined each year. Return on equity also indicates that financial performance is poor due to a decrease in the company’s net income caused by rising excise duties as a result of the COVID-19 pandemic, while consumer purchasing interest has declines due to the instability of the community’s economy.